Performance-Based Assessment to Measure Narrative Reading Literacy Skills of Fourth-Grade Students at SDN Petunggu - Ratnawati Ratnawati; Ida Nuraeni; Juniati Juniati; Gazali Gazali; Sukma Sukma (Journal of Educational Sciences, 2026)
This study aims to develop a valid, practical, and effective performance assessment instrument to measure fourth-grade students’ reading literacy skills at SDN Petunggu. The study is motivated by students’ low reading literacy and the limitations of conventional assessments that mainly measure surface-level understanding without capturing students’ thinking processes authentically. This research employed a Research and Development (R&D) approach by adapting the Borg & Gall model, which was modified into several stages: preliminary study, needs analysis, curriculum analysis, product planning, instrument draft development, expert validation, limited trial, and field trial. The developed instrument includes fable texts, performance tasks, answer sheets, and analytic scoring rubrics designed to assess students’ comprehension of narrative texts. Expert validation results indicated that the instrument was categorized as valid. Field trials involving 18 students showed a balanced score distribution, indicating the instrument’s ability to differentiate students’ literacy levels. The majority of students were categorized as Good and Very Good, with no indication of floor or ceiling effects. These findings demonstrate that the developed performance assessment effectively captures students’ narrative reading comprehension in a more comprehensive and authentic manner. Therefore, the instrument is considered appropriate as an alternative assessment tool aligned with the demands of the Independent Curriculum to improve the quality of reading literacy evaluation in elementary schools.